2008
DOI: 10.1128/jvi.01076-08
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Membrane-Anchored Flagellin into Influenza Virus-Like Particles Enhances the Breadth of Immune Responses

Abstract: We have designed a membrane-anchored form of the Toll-like receptor 5 ligand flagellin, the major proinflammatory determinant of enteropathogenic Salmonella, which was found to be glycosylated and expressed on cell surfaces. A chimeric influenza virus-like particle (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
179
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(189 citation statements)
references
References 66 publications
9
179
0
1
Order By: Relevance
“…Flagellar polymers thus activate TLR5 but to a lesser extent than flagellin monomers (59). A variety of heterologous prokaryotic, viral, and eukaryotic protein antigens have shown increased immunogenicity in mice following genetic fusion or chemical conjugation with flagellin (6,43,69).…”
mentioning
confidence: 99%
“…Flagellar polymers thus activate TLR5 but to a lesser extent than flagellin monomers (59). A variety of heterologous prokaryotic, viral, and eukaryotic protein antigens have shown increased immunogenicity in mice following genetic fusion or chemical conjugation with flagellin (6,43,69).…”
mentioning
confidence: 99%
“…Spodoptera frugiperda Sf9, Madin-Darby canine kidney (MDCK; ATCC PTA-6500), and RAW264.7 (ATCC TIB-71) cells were maintained as described previously (40). Mouse-adapted influenza A/PR/8/34 (A/PR8; H1N1) and A/Philippines/2/82 (A/Philippines; H3N2) viruses were prepared as described previously (28).…”
Section: Methodsmentioning
confidence: 99%
“…Both FliC and FljB share conserved N and C termini which form the flagellar filament backbone (22) and contain motifs recognized by TLR5. Previously, we have found that a membrane-anchored form of the Salmonella enterica serovar Typhimurium phase I flagellin (FliC) can be coincorporated into influenza VLPs as an adjuvant molecule (40). The variable central region of FliC has been found to be hyperimmunogenic and unnecessary for its TLR5 binding activity (35).…”
mentioning
confidence: 99%
“…[4][5][6][7][8] By various self-assembling reactions, antigens can be deposited onto the surfaces of nanoparticles at high density. 9 The repetitive antigen structures can act as multivalent ligands and can cross-link antigen receptors on immune cell surfaces for better targeting and long-term stimulation.…”
Section: Introductionmentioning
confidence: 99%